Perancangan Kursi Kerja yang Ergonomi untuk Pekerja di UKM Wintolo - Kartinasari Ayuhikmatin Sekarjati; Toto Rusianto; Andrean Emaputra; Argaditia Mawadati; Agus Hindarto Wibowo; Ichza Nur Amami; Rio Dewangga (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
UKM Wintolo is a small and medium business that produces molds using liquid aluminum as the base material. UKM Wintolo has 3 workers with different age ranges. When initial observations were made, it was seen that the position and posture of workers when working were not neutral and not ergonomic, so community service activities were carried out at UKM Wintolo with the theme of improving processes and work environments in accordance with ergonomics rules at UKM Wintolo. This activity was carried out for 2 days, namely the first day was carried out by providing socialization material according to the theme of the activity, and taking measurements using the anthropometric method in making work facilities. The work facilities that have been refurbished include work chairs that are used for the mold preparation process and the process of taking mold results. On the second day, the products that had been made for these two activities were handed over. Community service activities are carried out to avoid musculoskeletal disorder (MSDs) complaints and this will subsequently have an impact on increasing worker productivity. Through this activity, it can be seen that there is a change in the position and posture of workers while working.